Alge v velikem ali priobalnem jezeru v Fiesi, Slovenija - Krivograd-Klemenčič, Aleksandra (Natura Sloveniae, 2003)
In the years 1998, 1999 and 2000, samples were taken seasonally in the Fiesa lake situated next to the see - the only brackish lake in Slovenia. The purpose of the investigation was to establish qualitative species structure and relative abundance of the periphyton and the phytoplankton. In the years 1999 and 2000, some physical and chemical parameters were also measured. Altogether, 85 species and subspecies of algae (of six classes) were determined. Most of them belonged to Bacillariophyceae, followed by Cyanophyceae and Chlorophyceae. 19 species and subspecies are new to Slovenia,15 of which belong to Bacillariophyceae and 4 to Cyanophyceae. Most of the new species and subspecies belonging to the genus Navicula. This is thefirst research into the Fiesa coastal lake's periphyton and phytoplankton carried out through a longer period of time.
Keywords: Algae; Alge; braktična jezera; Ecosystem; Ekosistem; ekosistemi; Electric Conductivity; Električna prevodnost; Fiesa; Fitoplankton; Fresh Water; Kisik; Letni časi; Natrijev klorid; Oxygen; perifiton; Phytoplankton; Seasons; Sladka voda; Sodium Chloride; Temperatura; Temperature